Food quality and nutraceutical value of nine cultivars of mango (Mangifera indica L.) fruits grown in Mediterranean subtropical environment. (30th March 2019) - Gentile, Carla; Di Gregorio, Emanuela; Di Stefano, Vita; Mannino, Giuseppe; Perrone, Anna; Avellone, Giuseppe; Sortino, Giuseppe; Inglese, Paolo; Farina, Vittorio
Highlights: Mango fruit quality is affected by genotype and ripening stage at harvest. Fruits from the Mediterranean area achieve high quality attributes. Fruits ripened after harvest can achieve quality compatible with the market demand. UHPLC–MS/MS was used to identify and quantify the polyphenol profile. PCA coupled with chemical data allowed cultivar discrimination. Abstract: Mango ( Mangifera indica L.) quality is strongly influenced by genotype but individuating the most appropriate harvesting time is essential to obtain high quality fruits. In this trial we studied the influences of the ripening stage at harvest (mature-ripe or green-ripe) on quality of ready to eat mango fruits from nine cultivars ( Carrie, Keitt, Glenn, Manzanillo, Maya, Rosa, Osteen, Tommy Atkins and Kensington Pride ) grown in the Mediterranean subtropical climate through physicochemical, nutraceutical, and sensory analysis. Our results show a large variability among the different observed genotypes and in dependence of the ripening stage at harvest. With the exception of Rosa, mature-ripe fruits are well-colored, sweet and aromatic, and better suited for short supply chains. On the other hand, post-harvest ripened fruits are firmer, frequently ( Carrie, Glenn, Keitt, Manzanillo, Maya ) possess interesting nutraceutical value and, in the case of Glenn, Maya, Osteen, and Kensington Pride, they can reach market standard quality.